The Influence of Audit Opinion, Profitability, and Auditor Reputation on Auditor Switching: A Case Study of Transportation and Logistics Companies Listed on the Indonesia Stock Exchange (2019–2024) - Pramana Putra; Ajeng Luthfiyatul Farida (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study investigates the influence of audit opinion, profitability, and auditor reputation on auditor switching in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. Using a quantitative approach and binary logistic regression analysis, the research analyzes 132 firm-year observations obtained through purposive sampling. Audit opinion is measured based on whether a company receives a modified or unqualified opinion, profitability is assessed using Net Profit Margin (NPM), and auditor reputation is determined by affiliation with Big Four audit firms. The results indicate that audit opinion significantly influences auditor switching, whereas profitability and auditor reputation do not show a statistically significant impact. The findings support agency theory, which suggests that companies may change auditors following unfavorable opinions to minimize external scrutiny and restore investor confidence. The absence of influence from profitability and auditor reputation highlights that audit switching decisions in this sector are more reactive to audit outcomes than financial performance or branding considerations. This study contributes to the auditing literature by confirming the role of audit opinion in corporate governance and offering practical implications for regulators and stakeholders in monitoring audit quality and transparency within Indonesia’s logistics sector. Keywords: Audit Opinion, Auditor Reputation, Agency Theory, Logistic Regression